Role of peritoneal washing cytology in ovarian malignancies: correlation with histopathological parameters. Issue 1 (December 2015) - Naz, Samreen; Hashmi, Atif; Ali, Rabia; Faridi, Naveen; Hussian, Syed; Edhi, Muhammad; Khan, Mehmood
Abstract Background Peritoneal dissemination of ovarian tumors is a major prognostic parameter in ovarian malignancies. Analysis of peritoneal washing cytology serves as a useful predictor of ovarian surface involvement and peritoneal metastasis even in the absence of clinical omental spread. The aim of the current study is to correlate peritoneal cytology with various histologic features of ovarian cancers in our setup. Methods A total of 60 cases of ovarian tumors were included in the study that underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy and omental and lymph node sampling during 2009 till 2014 at the Liaquat National Hospital, Karachi. Any free abdominal fluid was aspirated at the time of surgery. In the absence of free fluid, peritoneal washing was done with 50–100 ml of normal saline. Four cytospin preparations were done along with a cell block preparation. Correlation of peritoneal cytology with various histologic parameters was performed. Results Out of the 60 cases of ovarian tumors involved in the study, 56 were surface epithelial tumors, 2 germ cell tumors, and 2 metastatic carcinomas. The mean tumor size was 9.6 cm. Capsular invasion was seen in 61 % of the cases, and omental metastasis in 51 % of the cases. Serous carcinoma was found to have a significantly higher frequency of positive peritoneal cytology (76.9 %) compared to endometrioid and mucinous carcinomas (44 and 25 %, respectively). A significant positive correlation was seen between positive peritoneal cytology and capsular invasion and omental metastasis with ap value of <0.001. Conclusions Positive peritoneal washing cytology has been implemented in ovarian cancer guidelines because of its prognostic significance in ovarian tumors. In addition to being an indicator of peritoneal metastasis, positive cytology also correlates with capsular invasion and histologic type in ovarian tumors. Therefore, it should always be used as an adjunctive tool in the surgical management of ovarian tumors.